(untitled) (Proceeding of SINERGY, 2026)
Indonesia’s digital transformation has increasingly influenced the administration of land registration and the professional functions of the Land Deed Official (Pejabat Pembuat Akta Tanah/PPAT). A central development within this transformation is the introduction of digitally executed PPAT deeds, which fundamentally challenges the traditional conception of authentic deeds that rely on physical presence, written form, and handwritten signatures. This shift raises critical legal issues concerning the validity, evidentiary force, and legal consequences of digital PPAT deeds within Indonesia’s civil law system. This paper examines the regulatory framework governing digital PPAT deeds in Indonesia and analyzes the extent to which current regulations support legal certainty and legal utility. Employing a normative juridical approach, the study analyzes statutory provisions, implementing regulations, and legal doctrines related to authentic deeds, electronic documents, and land registration administration. The analysis demonstrates that although digital land services and electronic documentation have been progressively introduced, the regulation of PPAT deeds remains only partially adaptive. This condition creates regulatory fragmentation and legal uncertainty, particularly regarding the classification of digital PPAT deeds as authentic deeds and their evidentiary value in judicial proceedings. The paper argues that regulatory innovation is essential to reconcile technological advancement with established legal principles. Digitalization should not be limited to administrative efficiency but must be accompanied by substantive and procedural legal reform, including clear norms on digital deed formation, authentication mechanisms, and the scope of PPAT authority in electronic transactions. Such regulatory reform is necessary to ensure that digital PPAT deeds provide not only operational efficiency but also reliable legal protection for the parties involved. By emphasizing the principles of legal certainty and legal utility, this study proposes a conceptual direction for regulating digital PPAT deeds that aligns technological innovation with the foundational values of Indonesian land law. The findings are expected to contribute to academic discourse and serve as a reference for policymakers in developing a coherent and sustainable legal framework for digital land administration in Indonesia.